COMMUNITY CAPACITY DEVELOPMENT THROUGH PROCESSINGORGANIC WASTE - Muh. Adnan Kasogi (Jurnal Pengabdian Masyarakat, 2024)
Waste management is a common problem experienced by urban communities. PageragungVillage, Walantaka, Serang City also experienced waste management due to the unavailability oflandfills and lack of public awareness in waste management. This condition makes some people discardwaste improperly. This service program aims to increase public awareness of the dangers of misuse inthe future. Awareness-raising does by utilizing household waste into liquid organic fertilizer to reducethe waste generated. This activity is carried out in June to early July 2019, which is part of the SerangRaya University KKM work program. This service program produces liquid fertilizer manufacturingequipment with raw materials for household waste using EM4 (Ef ective Microorganisms) bioactivators. The results of two trials obtained liquid fertilizer that can use for fertilizing plants, especiallyplants in the house yard. Long-term use of this equipment can reduce household waste and increase thefertility of community plants.